1984
DOI: 10.1080/02724936.1984.11748338
|View full text |Cite
|
Sign up to set email alerts
|

Neurological diseases as seen at the outpatient Paediatric Neurology Clinic in Benin City

Abstract: There is a paucity of literature about the pattern of neurological diseases in children attending out-patient departments in Africa. In this study more boys than girls presented at our clinic. Almost all the principal diseases seen are eminently preventable. There appears to be no effective immunization programme. There is need for epidemiological studies to ascertain the true incidence of subacute sclerosing panencephalitis in view of the high incidence of measles in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 3 publications
1
19
1
Order By: Relevance
“…A relatively high prevalence of drop attacks was found among epileptic cases in our study which was one point of departure from the findings in the other studies 9 . This is a unique finding in our study whose basis was investigated and needs further examination.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…A relatively high prevalence of drop attacks was found among epileptic cases in our study which was one point of departure from the findings in the other studies 9 . This is a unique finding in our study whose basis was investigated and needs further examination.…”
Section: Discussioncontrasting
confidence: 57%
“…However the reporting of the predominance of grand mal epilepsy was not consistent in the studies on children as the findings by Kotsopoulos's 6 and et al in USA who found partial seizures to be more frequent in children than grand mal epilepsy. It is not immediately clear why grand mal prevailed over partial seizures in our setting and in other African based reports 2,3,9 . It may be suggested that the partial seizures remain unnoticed and the patients sought medical attention when it had secondarily evolved into generalized tonic-clonic seizure and this is especially true in the absence of EEG investigation.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…It costs US$100-150 for a computed tomography scan; this is much more than the average monthly salaries of the greater population of Nigerians. 6,13 This has contributed to the low imaging rates for children with seizure disorders in Nigeria. 6,13 Most centers managing children with seizure disorders have access to electroencephalography.…”
Section: Tertiary-level Health Carementioning
confidence: 99%
“…The most common neurology disorders seen are seizure disorders and cerebral palsy, which have remained constant over the past 20 years. [6][7][8][9][10][11][12] Although virtually all the centers have access to neuroimaging studies, the cost of these studies is prohibitive and not affordable to most patients. It costs US$100-150 for a computed tomography scan; this is much more than the average monthly salaries of the greater population of Nigerians.…”
Section: Tertiary-level Health Carementioning
confidence: 99%